2012
DOI: 10.2147/ijn.s32475
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of a combination of nanoparticulate Fe3O4 and gambogic acid on phosphatidylinositol 3-kinase/Akt/Bad pathway of LOVO cells

Abstract: Background: The present study evaluated whether magnetic nanoparticles containing Fe 3 O 4 could enhance the activity of gambogic acid in human colon cancer cells, and explored the potential mechanisms involved. Methods: Cytotoxicity was evaluated by MTT assay. The percentage of cells undergoing apoptosis was analyzed by flow cytometry, and cell morphology was observed under both an optical microscope and a fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Over the past half-century, pharmacological studies have revealed that GA has strong antitumor activities against various tumors including human leukemia, hepatoma, oral, breast, gastric, pancreatic, prostate, epithelial cervical and lung cancer [9] , [12] , [13] . Recently, GA has also been reported to have a marked anti-tumor effect for CRC cells in vivo and in vitro [14] , [15] . Due to the wide spectrum of anti-tumor activity with minimal toxicity to normal cells, GA has been approved by the Chinese Food and Drug Administration for the treatment of various cancers and has finished phase II clinical trials [7] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past half-century, pharmacological studies have revealed that GA has strong antitumor activities against various tumors including human leukemia, hepatoma, oral, breast, gastric, pancreatic, prostate, epithelial cervical and lung cancer [9] , [12] , [13] . Recently, GA has also been reported to have a marked anti-tumor effect for CRC cells in vivo and in vitro [14] , [15] . Due to the wide spectrum of anti-tumor activity with minimal toxicity to normal cells, GA has been approved by the Chinese Food and Drug Administration for the treatment of various cancers and has finished phase II clinical trials [7] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Chitchumroonchokchai et al confirmed that MAG inhibits the proliferation of HT-29 cells and reduces the expression of BCL-2 and β-catenin [32]. Similarly, the cytotoxic effect of natural mangosteen xanthones and GA in colorectal cancer cells (LoVo) was confirmed by Fang and Yu [34,35]. Aisha et al observed that MAG not only increased apoptosis but also impaired migration, insert invasion, and xenograft tumor growth in HCT-116 colon cancer cells [36].…”
Section: Discussionmentioning
confidence: 92%
“…With magnetic hyperthermia, nanoparticles leaked into the cytoplasm and produced reactive oxidative species, which led to DNA and mitochondrial damage and protein oxidation. Fang et al37 proposed that magnetic nanoparticles increase the activation of the phosphatidylinositol 3-kinase/Akt/Bad pathway in LOVO cells, leading to the expression of cytochrome c, caspase 9, and caspase 3 proteins. Using TEM, we observed magnetic nanoparticles that were internalized into Y79 retinoblastoma cells.…”
Section: Discussionmentioning
confidence: 99%